The taxonomic status of the “forgotten” Bolivian snakes, Atractus balzani Boulenger 1898 and Atractus maculatus (sensu Boulenger 1896) (Serpentes: Dipsadidae) - Passos, Paulo; Sudré, Vinícius; Doria, Giuliano; Campbell, Patrick D. (Zootaxa, 2018)
The genus Atractus Wagler 1828 comprises almost 150 currently recognized species of cryptozoic snakes widespread in the Neotropics, occurring from Panama to northeastern Argentina (Passos et al. 2016a). Despite the publication of the descriptions of several new species within the last decade, the taxonomy of the genus is unclear in some instances. This is mainly due to the fact that a number of poorly delimited taxa still exist (Passos et al. 2018). The most frequent problem faced by taxonomist working with the genus Atractus is the lack of specimens available for several species, most of them only still being known from their types, a situation that considerably weakens the definition of species boundaries between closely related taxa (Passos et al. 2010a, 2013). More importantly, many of the previously recognized species may represent aberrant individuals with unusual or abnormal scale counts, anomalous azygous or fused cephalic plates, infrequent polychromatic patterns, or any combination of these states (see Passos et al. 2016b). In the course of a thorough taxonomic review of the genus (Passos 2008; Passos et al. 2018), an effort has been made to examine all of the available types (including those apparently lost or misplaced in collections) and material of historical importance that was previously referred to the genus in the literature, and these were then compared to newer samples collected more recently. During the examination of the collections of the Natural History Museum of London and the Museo Civico di Storia Naturale of Genova, we found important specimens of Atractus from Bolivia. However, in order to better understand all the problems related to these old and “forgotten” Bolivian snakes, we need to examine their history.